Adenosylhopane Biosynthesis by the Radical SAM Enzyme HpnH†. Issue 2 (18th January 2020) - Zhong, Yuting; Ji, Xinjian
Abstract : Recently, we reconstituted the in vitro activity of a radical SAM enzyme HpnH, which catalyzes the adenosylation of hopene to produce adenosylhopane.